Turbulence modeling in engineering applications - Amorim, J. C C [UNESP] (My University, 1996)
A brief review is given of turbulence models in use today for engineering applications. The main categories covered are simple eddy-viscosity models, the k-ε two-equation model and Reynolds-stress-equation models as well as their algebraic stress derivatives. Calculation examples are presented for a variety of 2D and 3D flows.
Keywords: eddy; modeling; Reynolds stress; turbulence; viscosity; flow modelling